OPTIMALISASI PROSEDUR PEROLEHAN HAK KEKAYAAN INTELEKTUAL DALAM PERLINDUNGAN INOVASI PRODUK KESEHATAN DI INDONESIA - Jajang Arifin; Kodrat Alam (Universitas Wiralodra, 2025)
Intellectual property rights for health products constitute a crucial instrument in protecting innovation within the pharmaceutical and medical device sectors. In Indonesia, the acquisition procedure for intellectual property rights in health products encounters various obstacles that impede innovation effectiveness and commercialization processes. This analysis endeavors to identify and examine problems occurring in intellectual property rights acquisition procedures for health products, while providing recommendations for optimization. The research employs normative juridical methodology with a conceptual approach through examination of prevailing regulations and doctrines. Findings indicate that procedural complexity, extended processing duration, inadequate socialization, and coordination deficiencies among institutions represent primary impediments. Proposed solutions encompass procedural simplification, digital system implementation, capacity enhancement for human resources, and regulatory harmonization.